FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN USER TERHADAP PENERAPAN QUICK RESPONSE INDONESIA STANDARD SEBAGAI TEKNOLOGI PEMBAYARAN PADA DOMPET DIGITAL - Rina Mayanti (Jurnal Ilmiah Ekonomi Bisnis, 2020)
Quick Response Indonesia Standard (QRIS) is the QR Code which is standardized by Bank Indonesia as the technology used for the cashless payment method. It has been released officially since January 2020. The aim of this standardization is to provide an easier and more efficient payment method by QR Code technology. The electronic wallet's providers which are already implemented QRIS as their payment technology are Go-Pay and OVO. The goal of this research is to predict the factors affecting the user acceptance of QRIS implementation as the electronic wallet’s payment technology. The user acceptance regarding the QRIS implementation is predicted by user technology acceptance model called UTAUT 2. The variables used in this research are all UTAUT 2 model variables except age, gender, experience, and price value. The method used for analysing the data in this research is PLS-SEM. The result of this research shows that the facilitating conditions and hedonic motivation affect the user's behavioral intention for using QRIS as their payment technology, and this behavioral intention also gives the effect to their use behavior.